2004
DOI: 10.1016/j.ajic.2004.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing hospital preparedness using an instrument based on the Mass Casualty Disaster Plan Checklist: Results of a statewide survey

Abstract: Hospital mass casualty preparedness efforts were in an early stage of development at the time of this survey, and some critical capabilities, such as isolation, decontamination, and syndromic surveillance were clearly underdeveloped. Preparedness planning was more advanced among hospitals located in MMRS counties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 11 publications
3
86
1
1
Order By: Relevance
“…Higgins and colleagues, using the Mass Casualty Disaster Plan checklist, found in 2002 that hospital preparedness in Kentucky was clearly undeveloped and in the early stage of planning, with planning more developed in those counties participating in the Metropolitan Medical Response System (MMRS) program. (Higgins et al 2004) This reflects the situation we observed. While planners, for the most part, were committing a significant effort in trying to develop a pandemic influenza plan, and in fact had made large strides over the previous year, the plans developed were still crude and required much more work.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Higgins and colleagues, using the Mass Casualty Disaster Plan checklist, found in 2002 that hospital preparedness in Kentucky was clearly undeveloped and in the early stage of planning, with planning more developed in those counties participating in the Metropolitan Medical Response System (MMRS) program. (Higgins et al 2004) This reflects the situation we observed. While planners, for the most part, were committing a significant effort in trying to develop a pandemic influenza plan, and in fact had made large strides over the previous year, the plans developed were still crude and required much more work.…”
Section: Discussionsupporting
confidence: 59%
“…(Richards et al 2000;Derlet, Richards, and Kravitz 2001) The Community Tracking Study project found in 2006 that the standby capacity of hospitals to deal with emergencies was lacking. (Katz, Saiti, and McKenzie 2006) Likewise, studies of Kentucky hospitals (Higgins et al 2004) and nationwide (Crosse et al 2003) found significant gaps in the ability of hospitals to meet the demands of a public health emergency. Capacity shortfalls have been noted in emergency departments, intensive care beds, and general medical/surgical beds.…”
Section: Building Surge Capacitymentioning
confidence: 99%
“…Based on a fourstate survey by Wetter et al, overall preparedness is inadequate: fewer than 20% of hospitals have plans for a chemical or biological attack, and only 64% stock enough antibiotics to treat 50 cases of anthrax (2,9). A 2004 survey of 116 hospitals in Kentucky shows that only 50% have any type of decontamination facility, and only 19% report that their plans identify the need for more isolation beds (1). Less than one-third participate in community or regional stockpiles of pharmaceuticals, and one-fourth maintain a separate cache of antibiotics to treat staff in the event of a bioterror incident.…”
Section: Introductionmentioning
confidence: 97%
“…The US Federal Government distributed $135 million during fiscal year 2003 at the state level through the Bioterrorism Hospital Preparedness Program. States were required to assess hospital preparedness and develop regional response protocols (1). However, no studies have specifically addressed ED staff willingness to provide this emergent care based on the type of disaster, nor have any addressed which factors are most important in the decisionmaking regarding the willingness to work in a disaster setting.…”
Section: Introductionmentioning
confidence: 99%
“…Highly-knowledgeable nurses tend to involve more in the preparedness process [15,36], are professionally more accountable, possess more comprehensive response plans and present more accurate response behaviors. The higher the nurses' level of knowledge and skills, the swifter the measures taken [14,36,46,47].…”
Section: Consequencesmentioning
confidence: 99%